Home is where the heart is? How regional identity hinders internal migration in Germany - Anna Kremer (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2020)
People are emotional about places. I study the effect of regional identity (home") on internal migration ows in Germany between 1995 and 2017. Regional identity is proxied by measuring how NUTS3 regions were historically affiliated in the former patchwork of Germany. When controlling for the in uence of distance, culture (mea- sured by dialects) and regional characteristics, I confirm that regional identity drives migration patterns additionally. Employing the separation effect by the German wall affirms that not only earlier migration or family bonds determine movements instead of regional identity.
urn:nbn:de:bsz:14-qucosa2-721720
Keywords: R; R23; Z10; J61; 330; Internal migration; Regional identity; Historical belonging; Gravity model; Germany; Binnenmigration; Regionale Identität; Historische Zugehörigkeit; Heimat; Gravitationsmodell; Deutschland